Complementary mutations in an antigenic peptide allow for crossreactivity of autoreactive T-cell clones - Ausubel, Lara J. (The National Academy of Sciences of the USA, 1996)
T cells recognize antigen by formation of a trimolecular complex in which the T-cell receptor (TCR) recognizes a specific peptide antigen within the groove of a major histocompatibility complex (MHC) molecule. It has generally been assumed that T-cell recognition of two distinct MHC–antigen complexes is due to similarities in the three-dimensional structure of the complexes. Here we report results of experiments examining the crossreactivity of TCRs recognizing the myelin basic protein peptide MBPp85–99 and several of its analogs in the context of MHC. We demonstrate that single conservative amino acid substitutions of the antigenic peptide at the predominant TCR contact residues at positions 91 and 93 totally abrogate reactivity of specific T-cell clones. Yet, when a conservative substitution is made at position 91 concomitant with a substitution at position 93, the T-cell clones regain reactivity equivalent with that of the original stimulating peptide. Thus, the exact nature of the amino acid side chains engaging one TCR functional pocket may change the apparent selectivity of the other predominant TCR functional pocket, thus suggesting a remarkable degree of receptor plasticity. This ability of the TCR–MHC–peptide complex to undergo conformational changes provides a conceptual framework for reconciling the apparent paradox of the extreme selectivity of the TCR and its remarkable crossreactivity with different MHC–peptide complexes.